The effect of petrol subsidy removal on price of selected food items / Mohd Abas Mohd Othman - Mohd Othman, Mohd Abas (2016)
The government had gradually reduced aiding subsidy on fuel since July 2010 until December 2014 as part of the 10th Malaysian Plan (2010-2015) with the purpose to lower its budget and improve efficiency of the society’s welfare. The removals of subsidy on petrol indicate the price of petrol itself to increase in which it may lead to an increase in the costs of other goods and services based on the cost-push inflation theory. The main focused of this study was to discover the effects on the price of selected food items such as beef, chicken, rice and flour due to the increase in price of RON 95 petrol. There are four simple regressions for each of the items namely average monthly price of beef, chicken, rice and flour as dependent variables and price of RON 95 petrol as the proxy for subsidy removal. The data obtained from all the variables are of monthly data starting from June 2010 until December 2014 and were analyzed using SPSS software. The results show there are significant relationships between the price of RON 95 petrol and the prices of beef, chicken, rice and flour which proved that the removals of subsidy on petrol had effected the rise in the cost of the selected food items. However, there are sign of coefficients which are not consistent with economic theory regarding the price of rice and flour after all this can be explained by the fact that these two items are under the pricing control mechanism of the government. Overall, the study suggests the models are reliable for further studies in the future